Evaluating efficiency of Islamic banks using data envelopment analysis: international evidence - Mohd Tahir, Izah; Abu Bakar, Nor Mazlina; Haron, Sudin (Islamic Bank Training and Research Academy, Islamic Bank Bangladesh Limited, 2011)
This study investigates the efficiency of Islamic banks in four regions; Africa, the Far East and Central Asia, Europe and the Middle East during the period of 2003-2008. The non-parametric approach, Data Envelopment Analysis is utilised to analyse the technical and scale efficiencies of Islamic banks. Overall, the results suggest that mean efficiency of Islamic banks have declined over the period from 0.746 in 2003 to 0.544 in 2008. During the period of study, our results suggest that pure technical inefficiency has largely resulted in the overall inefficiency of Islamic banks. Using a series of parametric and non-parametric tests, our results indicate that there are significant differences in efficiencies between size and not between regions. Large sized banks tend to be efficient than the small and medium sized banks.